2012 25th IEEE Canadian Conference on Electrical and Computer Engineering (CCECE) 2012
DOI: 10.1109/ccece.2012.6334856
|View full text |Cite
|
Sign up to set email alerts
|

A formal and empirical analysis of recombination for genetic algorithm-based approaches to the FPGA placement problem

Abstract: To reduce the compilation times for Field Programmable Gate Arrays, genetic algorithms have been proposed for performing placement. However, the quality of solutions produced by these methods, so far, has been inferior to that produced by other search methods. In this paper, we show how traditional recombination operators, employed by the genetic algorithm when performing placement, fail to produce offspring solutions that are confined to the solution subspace defined by the parent solutions. This violates a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…FPGA placement maps a clustered logical circuit to an array of ixed physical components to optimize routing area, critical path, power eiciency, and other metrics. FPGA placement algorithms can be broadly classiied into four categories: (1) classic min-cut partitioning [32,33,46], (2) popular simulated-annealing-based methods [2,3,23,31], (3) analytical placement currently used in FPGA CAD tools [1,12,15,28], and (4) esoteric evolutionary approaches [7,20,47]. Min-cut algorithm worked well on small FPGA capacities by iteratively partitioning the circuit to spread the cells across the device.…”
Section: Fpga Placementmentioning
confidence: 99%
“…FPGA placement maps a clustered logical circuit to an array of ixed physical components to optimize routing area, critical path, power eiciency, and other metrics. FPGA placement algorithms can be broadly classiied into four categories: (1) classic min-cut partitioning [32,33,46], (2) popular simulated-annealing-based methods [2,3,23,31], (3) analytical placement currently used in FPGA CAD tools [1,12,15,28], and (4) esoteric evolutionary approaches [7,20,47]. Min-cut algorithm worked well on small FPGA capacities by iteratively partitioning the circuit to spread the cells across the device.…”
Section: Fpga Placementmentioning
confidence: 99%
“…al. [4] [19] has found that GAs for FPGA placement are not yet comparable to SA implementations mainly due to the weakness of the crossover operator. Collier has proposed a CSR crossover operator, which they experimentally show is better than the PMX originally proposed by Goldberg for the traveling salesman problem [20].…”
Section: B Gas For Fpga Placementmentioning
confidence: 99%
“…Uncommon attributes of an individual may still be used to "fish-out" a person's identity, even though one may not know their name, phone number, or address explicitly from a database [4][5] [6] [7].…”
Section: A Backgroundmentioning
confidence: 99%